Rancang Bangun Aplikasi Pelayanan Pelanggan Air Bersih Berbasis Android Pada Bumdes Lantongau - Indra Ava Dianta; Danang Danang; Nusril Nusril (STEKOM PRESS, 2022)
BUMDES Lantongau is one of the Lantongau Village-Owned Enterprises whose one line of business is to distribute clean water needs in four villages, namely Lantongau Village, Morikana Village, Katukobari Village, and Lakorua Village. In order to facilitate the registration process, meter recording, payment bills, service interruption information, and customer complaints, applications that facilitate all service processes. Therefore, the most suitable application is using an Android-based application, the use of an Android-based application is an option because almost all customers have an Android device, so that services can be directly carried out quickly, easily, effectively and efficiently. With this application, it is easier for the customer and the BUMDES Lantongau in services ranging from customer registration, meter recording, billing payments, customer complaints and information on service disruptions, all can be done through the application. This application is designed using android studio with Research and Development (R&D) development method Keywords: Android Application, Customer Service, BUMDES Lantongau